ACR Appropriateness Criteria® Management of Recurrent Endometrial Cancer. (October 2016) - Elshaikh, Mohamed A.; Vance, Sean; Gaffney, David K.; Biagioli, Matthew; Jhingran, Anuja; Jolly, Shruti; Kidd, Elizabeth; Lee, Larissa J.; Li, Linna; Moore, David H.; Rao, Gautam G.; Wahl, Andrew O.; et al.
Abstract : Objectives: In women with endometrial carcinoma (EC), tumor recurrences tend to occur in the 2- to 3-year period following surgical staging. Management of disease recurrence in EC poses significant challenges. These patients represent a heterogenous group where histologic subtypes, previous adjuvant management, interval since completion of adjuvant therapy, and size and site(s) of disease recurrence all have important implications on salvage therapies and prognosis. No randomized controlled trials have been published to determine optimal management in this group of patients. An expert panel was convened to reach consensus on the most appropriate management options in this group of patients. Methods: The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment. Results: Five clinical variants were developed to address common scenarios in the management of women with recurrent EC. Group members reached consensus on the appropriateness of specific evaluation and treatment approaches with numerical ratings. Conclusions: In combining available medical literature and expert opinions, this manuscript may serve as an aid for other practitioners in the appropriate management of women with recurrent EC.